Enterobacteria - Bhonchal Bhardwaj, Sonia (IntechOpen, 2022)
Enterobacteriaceae are a large family of Gram-negative bacteria including Escherichia, Salmonella, Shigella, Klebsiella, Yersinia, and others. They are associated with intestinal and extra-intestinal diseases, such as urinary tract infections and diarrhea. This book examines enterobacteria with a focus on pathogenesis, virulence factors, and treatment strategies, as well as their role in multidrug resistance.